2019
DOI: 10.3847/1538-4357/ab15d7
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Properties of Coronal Shock Waves with Those of Solar Energetic Particles

Abstract: We develop and exploit a new catalog of coronal pressure waves modeled in 3D to study the potential role of these waves in accelerating solar energetic particles (SEPs) measured in situ. Our sample comprises modeled shocks and SEP events detected during solar cycle 24 observed over a broad range of longitudes. From the 3D reconstruction of shock waves using coronagraphic observations we derived the 3D velocity along the entire front as a function of time. Combining new reconstruction techniques with global mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 64 publications
4
98
0
Order By: Relevance
“…Recent studies have also found evidence that the highest energy particles could be accelerated when strong shocks reach the tip of streamers (e.g. Rouillard et al 2016;Kouloumvakos et al 2019). The next decade of research with PSP and the Solar Orbiter promises to be rich in new discoveries on streamer flows.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also found evidence that the highest energy particles could be accelerated when strong shocks reach the tip of streamers (e.g. Rouillard et al 2016;Kouloumvakos et al 2019). The next decade of research with PSP and the Solar Orbiter promises to be rich in new discoveries on streamer flows.…”
Section: Resultsmentioning
confidence: 99%
“…MAST is an MHD model developed by Predictive Sciences Inc. that makes use of the photospheric magnetograms from SDO/HMI as the inner boundary condition of the magnetic field and includes detailed thermodynamics with realistic energy equations accounting for thermal conduction parallel to the magnetic field, radiative losses, and parameterized coronal heating. Using the plasma and magnetic field proper-ties provided from the MAST model of Carrington rotation 2194 (CR2194: starting from 2017-08-16 11:13, ends at 2017-09-12 17:15) and shock reconstructions, we determine in 3-D and along the entire shock front the upstream shock Mach numbers (Alfvénic M A and fast magnetosonic M fm ), density compression ratio (X), and the shock geometry θ BN which is defined as the magnetic field obliquity with respect to the shock normal (see Kouloumvakos et al 2019, for a detailed description of the techniques). This modeling is performed with a temporal resolution of one minute, from the low corona to IP space at ∼150 R (i.e.…”
Section: Shock Wave Reconstruction 3dmentioning
confidence: 99%
“…In determining the evolution of the shock wave parameters at regions well-connected to Earth we use the methods presented in Kouloumvakos et al (2019) and also in our discussions in Sections 3 and 4. The shock wave intersected magnetic field lines that were wellconnected to Earth at 15:57 UT and it became supercritical around 15:59 UTl 3 .…”
Section: Connecting the Shock Evolution With The Time History Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, flare science remains quite healthy 26 years later.However, improving measurements made the shock acceleration of gradual SEPs increasingly difficult to ignore [1,[8][9][10][11][12][13]. These included onset timing of SEPs [14,15], multi-spacecraft studies [16] with improved shock imaging [17][18][19][20][21][22], temperature and ionization-state measurements [13,[23][24][25][26][27][28], shock modeling [24][25][26][27][28][29][30][31][32][33][34][35], and correlations of SEP intensities with CME speed [22,36], which continued to strengthen the evidence [1,34].Meanwhile, there was early evidence for a completely different kind of SEP event being first noted by the abundance of the isotope 3 He, which was enhanced by orders of magnitude. The ratio 3 He/ 4 He ≈ 5×10-4 in the solar wind, but Serlemitsos and Balasubrahmanyan [37] found 3 He/ 4 He = 1.52 ± 0.10 in a small SEP event, completely unaccompanied by any 2 H, 3 H, Li, Be, or B (Be/O and B/O < 4×10-4 ), failing to suggest any evidence of nuclear fragmentation at all.…”
mentioning
confidence: 99%